An Investigation of Pulp Mill Effluents and Their Wood Feedstocks as Potential Neuroendocrine Disruptors of the Fish Reproductive Axis - Waye, Andrew (Université d'Ottawa / University of Ottawa, 2015)
Common observations of reduced gonad size and spawning inhibition in wild and laboratory raised fish exposed to pulp mill effluents indicate that reproductive neuroendocrine signalling pathways may be upset. This thesis supported the neuroendocrine disruption of reproduction hypothesis by identifying potential disruptors and targets where these impacts may occur. A mechanistic study of the in vivo fathead minnow (FHM) spawning assay used by industry to assess effluent quality showed that ovulation, but not milt production, was impaired. This finding supported the hypothesis that the neuroendocrine cascade that triggers ovulation may be disrupted. I hypothesized that neuroactive constituents previously described in effluents were originating in wood feedstocks and neuroactive extracts of hardwood and conifer feedstocks were identified. Phytochemicals associated with effluents were neuroactive. Structurally similar phenolic phytochemicals showed monoamine oxidase (MAO) inhibition, and resin acid diterpenes displayed glutamic acid decarboxylase (GAD) inhibition. Inhibitors of these enzymes may have impacts on the control of reproduction since MAO metabolizes dopamine, an inhibitor of the neuroendocrine reproductive axis, while GAD synthesizes -aminobutyric acid (GABA), a stimulator of this axis. Bioassay-guided fractionations of effluents and wood feedstocks identified that medium polar extracts of primary- and secondary-treated effluents and balsam fir feedstock contained high GAD inhibitory activity. This activity was associated with chemically complex fractions rather than single active principles. Advanced metabolomic comparison of medium polar extracts of feedstock and treated effluent identified 15 common plant metabolites, demonstrating that phytochemicals entering the mill in wood are surviving pulp production and effluent treatment processes and may be responsible for observed GAD inhibition. Discriminant metabolomics analysis identified 4-acetylpyridine, a novel compound to be described in effluents, as well as two other tentatively identified compounds, as chemical markers of GAD inhibitory effluent fractions. Five tentatively identified chemical markers and (+)-lariciresinol were found in inhibitory balsam fir feedstock fractions. Neuroendocrine pathways that control reproduction in fish, such as dopamine and GABA pathways, are also important drug targets for the treatment of neurological disorders in mammals; therefore these results also have implications for the development of natural health products from phytochemicals and tree extracts common to Canadian forests. By using an interdisciplinary approach (phytochemistry, neuroendocrinology, ecotoxicology), I was able to explore the various implications of my research on the fields of natural health products chemistry and aquatic toxicology.
Keywords: Neuroendocrinology; Phytochemistry; Fish reproduction; Natural health products; Ecotoxicology; Aquatic toxicology; Metabolomics; Reproductive hormone axis